The impact of human capital index on economic growth in Malaysia - Noorziah Mohd Salleh; Imbarine Bujang; Christina Andin; Mohammad Nur Azhar Mazlan (MDPI, 2022)
The purpose of this study was to investigate the impact of the human capital index (HCI) on economic growth (EG). Despite a consistent pattern between human capital capabilities and economic growth, there was no significant correlation between HCI and EG, while employment was positively correlated. HCI improves both labor force education and the health care commitment of a nation, two important factors affecting employment. Accordingly, the country’s human capital development plan should improve the health and education of its citizens, including monitoring their health closely and providing quality education to students. In this study, we explore the relationship between human capital index accumulation (health and education) and economic growth in Malaysia by using a Dickey–Fuller test with an Augmented protocol from 1979 and Phil perrons tests from 1988, which have been conducted.